MODEL PREDATOR-PREY DENGAN DUA PREDATOR - Danar Agus Nugroho; Rina Reorita (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2013)
This paper discussed about the predator-prey model with two predators. This model is a development of the model given by Korobeinikov and Wake (1999). Dynamic behavior of the model can be determined based on the stability of the equilibrium point. The stability of the equilibrium point of predator-prey model with two predators on the general ecosystem shows that there is no coexistence state (grown in tandem) on both predators and for a long time one of the predators will lead to the local extinction even though there is no competition between the two predators. Furthermore, this model is applied to the brown plant hopper predator, mirid prey and tomcat prey. The result shows that the population of brown planthopper and both of the predators will oscillate towards a particular value with a shorter span of time. In the long term, the number of brown planthopper and mirid will be heading to the equilibrium point, while the tomcat will lead to local extinction.